(untitled) (Archives of Clinical Psychiatry, 2007)
BACKGROUND: Several Brazilian scientists have been studying the relationship between religiousness and mental disorders for more than one century. However, currently, those works are poorly known. OBJECTIVES: to present an overview of past and current Brazilian studies on mental health and religion. METHODS: Analysis of historically important research, as well as current investigation on mental health and religion in Brazil. RESULTS: These studies started in Brazil by the end of XIX Century usually focusing on messianism and collective forms of "religious insanity". Current studies deal with topics like religion and alcohol or drug use, as well as several clinical issues like schizophrenia and suicide. This research line lacks a better integration between empirical work and theoretical analysis data. There is also a need of a closer dialogue with social sciences such as anthropology and sociology of religion. CONCLUSIONS: These Brazilian studies on religiousness and mental health encompass a wide variety of subjects and methods. The search for theories to guide empirical studies and a more effective integration with social sciences would contribute to the development of this field.